'Halo-kinematic' sequence stratigraphic analysis adjacent to salt diapirs in the deepwater contractional province, Liguro-Provençal Basin, Western Mediterranean Sea. (May 2020) - Mianaekere, V.; Adam, J.
Abstract: This study investigates the coupled halokinetic and depositional processes of the contractional diapiric-minibasin province in the distal deepwater Liguro-Provencal basin. The Liguro-Provencal basin is situated above young oceanic crust developed during the NW-SE Miocene rifting and back-arc extension. The Messinian evaporite succession was deposited contemporaneously on extended continental crust and young oceanic crust. Post-Messinian postrift isostatic adjustments of the continental shelves influenced prograding sedimentary wedges, gravitational failure and gravity-driven deformation above salt, hence extensive salt diapirism is situated in a contractional domain in the deepwater basin overlying oceanic crust. The kinematic evolution of salt structures in the contractional province is analysed from preserved depositional patterns in successive genetic depocenters adjacent to salt diapirs. Within minibasin successions, four dominant depositional patterns have been classified as a layered, truncated-onlap wedge, onlap-wedge and truncated-hook. The truncated-onlap wedge sequences are early syn-kinematic depositional packages contemporaneous to salt growth and may converge towards the rising salt structure prior to diapirism. They are therefore categorised as the pre-diapiric sequence. The onlap wedge and truncated-hook styles form later syn-kinematic packages in diapiric growth phase and are labelled as halo-kinematic sequences. The layered sequence, maybe pre-kinematic and shows parallel beds all truncating on the diapir flank. This onlap wedge consists of on-lapping beds at the basal sequence boundary, stratal thinning or convergence towards the diapir flank and angular truncations on an erosional surface on the top depositional boundary proximal to the diapir flank. The truncated-hook sequence reflects an absence of beds on-lapping on the diapir roof within the sequence, beds truncate at the diapir flank and on an erosional/slip surface on top depositional boundary proximal to the diapir flank. The truncated-onlap wedge sequence reflects on-lapping beds in the middle of the sequence and older and younger beds that truncate on the top depositional boundary. Highlights: Preserved seismic stratigraphic patterns in successive genetic depocenters adjacent to salt diapirs show the kinemtaic evolution of salt structures. Minibasin stratigraphic fill are classified as as pre-kinematic pre-diapiric and halo-kinematic sequence packages to infer kinematic stages of salt growth. Unique stratal (depositional) patterns; layered, onlap wedge, truncated hook and truncated onlap wedge sequences directly infer kinematic growth phases of salt growth. Wheeler diagrams demonstrate temporal halokinetic processes that form the unique stratal depositional patterns at local scale.